2022
DOI: 10.2169/internalmedicine.7533-21
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoid-like Granulomatous Lung Disease with Subacute Progression in Silicosis

Abstract: A 67-year-old man was admitted to our hospital with cough and fatigue. He had had long-term exposure to silica due to cement processing. Chest computed tomography showed bilateral centrilobular nodules, and hilar and mediastinal lymphadenopathy with calcification, suggesting chronic silicosis. Within a few months, these nodules enlarged, and bilateral patchy consolidations appeared. A lung biopsy revealed sarcoid-like granulomas with birefringent particles under polarized light without malignancy or infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These criteria are: clinical presentation compatible with sarcoidosis, the presence of non-necrotizing granulomatous inflammation in one or more tissue samples, and the exclusion of alternative causes of granulomatous disease [19]. Various causative agents have been linked to sarcoidosis, including silica-containing cat litter [7,14]. Many features were consistent with sarcoidosis in the current case, mainly the calcitriol meditated hypercalcemia and the good response to steroid therapy.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These criteria are: clinical presentation compatible with sarcoidosis, the presence of non-necrotizing granulomatous inflammation in one or more tissue samples, and the exclusion of alternative causes of granulomatous disease [19]. Various causative agents have been linked to sarcoidosis, including silica-containing cat litter [7,14]. Many features were consistent with sarcoidosis in the current case, mainly the calcitriol meditated hypercalcemia and the good response to steroid therapy.…”
Section: Discussionmentioning
confidence: 61%
“…Exposure to silica dust is one of the oldest known causes of pulmonary diseases, and is associated with a variety of occupations, such as construction, quarrying, and chemical industries [1]. While the inhalation of fine silica particles is a well-recognized risk factor for silicosis, several studies have reported an association between silica exposure and sarcoidosis or sarcoid-like granulomatous lung diseases [2][3][4][5][6][7][8]. According to the literature, silica exposure may also be a trigger for other conditions, including hypersensitivity pneumonitis (HP), lung cancer, tuberculosis, chronic obstructive pulmonary disease, and kidney disease [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The surgical biopsy demonstrated that multiple sarcoid-like granulomas were composed of clustered epithelioid and multinucleated giant cells, while the silica nodules were mainly composed of dust-laden hyalinized collagen, and pathologic findings of aluminous showed diffuse interstitial fibrosis with emphysema. Recent case reports have postulated that sarcoid-like granulomatous lung disease can also be induced by silicates ( 21 , 22 ). Different epidemiological studies have demonstrated a higher risk of sarcoidosis among persons occupationally exposed to silica ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis is a multisystem granulomatous disease of unknown aetiology whose immunological mechanism has not yet been identified [ 24 ]. This fact has led some authors to establish the diagnosis of sarcoidosis from the exclusion of other sarcoid-like diseases, according to its clinicopathological findings [ 25 ]. Siderosis is a benign pneumoconiosis that develops as a result of exposure to metallic iron or iron oxide dust [ 26 ].…”
Section: Introductionmentioning
confidence: 99%